Ta‘līm al-Lughah al-‘Arabīyah fī Ghana: al-Taḥaddīyāt wa-al-Ḥulūl - Abbas Shamsuddin Ibrahim (Al-Ma‘rifah, 2018)
The research on the subject of Arabic language education in Ghana addresses challenges and solutions. It highlights the challenges faced by Arabic language education in Ghana from (al-kuttab), schools, institutes, and universities, and presents possible solutions to challenges through the use of the analytical and analytical approach. Living in Ghana, with no official bodies responsible for the development of Arabic in schools, the development of curriculum development and development, the status and development of teachers, and the lack of adequate support from Arab countries for Arabic, as do their counterparts in Ghana, such as French and Germans And its Chinese and other living languages that seek to revive their language at the official level